Phase, current, absorbance, and photoluminescence of double and triple metal ion-doped synthetic and salmon DNA thin films. (11th September 2017) - Chopade, Prathamesh; Dugasani, Sreekantha Reddy; Kesama, Mallikarjuna Reddy; Yoo, Sanghyun; Gnapareddy, Bramaramba; Lee, Yun Woo; Jeon, Sohee; Jeong, Jun-Ho; Park, Sung Ha
Abstract: We fabricated synthetic double-crossover (DX) DNA lattices and natural salmon DNA (SDNA) thin films, doped with 3 combinations of double divalent metal ions (M 2+ )-doped groups (Co 2+ –Ni 2+, Cu 2+ –Co 2+, and Cu 2+ –Ni 2+ ) and single combination of a triple M 2+ -doped group (Cu 2+ –Ni 2+ –Co 2+ ) at various concentrations of M 2+ ([M 2+ ]). We evaluated the optimum concentration of M 2+ ([M 2+ ]O ) (the phase of M 2+ -doped DX DNA lattices changed from crystalline (up to ([M 2+ ]O ) to amorphous (above [M 2+ ]O )) and measured the current, absorbance, and photoluminescent characteristics of multiple M 2+ -doped SDNA thin films. Phase transitions (visualized in phase diagrams theoretically as well as experimentally) from crystalline to amorphous for double (Co 2+ –Ni 2+, Cu 2+ –Co 2+, and Cu 2+ –Ni 2+ ) and triple (Cu 2+ –Ni 2+ –Co 2+ ) dopings occurred between 0.8 mM and 1.0 mM of Ni 2+ at a fixed 0.5 mM of Co 2+, between 0.6 mM and 0.8 mM of Co 2+ at a fixed 3.0 mM of Cu 2+, between 0.6 mM and 0.8 mM of Ni 2+ at a fixed 3.0 mM of Cu 2+, and between 0.6 mM and 0.8 mM of Co 2+ at fixed 2.0 mM of Cu 2+ and 0.8 mM of Ni 2+, respectively. The overall behavior of the current and photoluminescence showed increments as increasing [M 2+ ] up to [M 2+ ]O, then decrements with further increasing [M 2+ ]. On the other hand, absorbance at 260 nm showed the opposite behavior. Multiple M 2+ -doped DNA thin films can be used in specific devices and sensors with enhanced optoelectric characteristics and tunable multi-functionalities.